Beyond hubris: How highly confident entrepreneurs rebound to venture again - Hayward, Mathew L.A.; Forster, William R.; Sarasvathy, Saras D.; Fredrickson, Barbara L. (Journal of Business Venturing, 2010)
This article outlines why highly confident entrepreneurs of focal ventures are better positioned to start and succeed with another venture; and therefore why overconfidence in one's capabilities functionally persists and pervades amongst entrepreneurs. By combining cognitive perspectives on confidence in decision making with Fredrickson's [Fredrickson, B.L. 1998. What good are positive emotions?. Review of General Psychology, 2, 300–319.; Fredrickson, B.L. 2001. The role of positive emotions in positive psychology: the broaden-and-build theory of positive emotions. American Psychologist, 56, 218–226.; Fredrickson, B.L. 2003. The value of positive emotions. American Scientist, 91: 330–335] ‘broaden-and-build’ theory of positive emotions, this paper elaborates the manner in which such entrepreneurs can develop emotional, cognitive, social and financial resilience that can be marshaled and mobilized for a subsequent venture.